Driving With Distraction: Measuring Brain Activity and Oculomotor Behavior Using fMRI and Eye-Tracking - Yuen, Nicole H.; Tam, Fred; Churchill, Nathan W.; Schweizer, Tom A.; Graham, Simon J. (Frontiers in Human Neuroscience, 2021)
Introduction: Driving motor vehicles is a complex task that depends heavily on how visual stimuli are received and subsequently processed by the brain. The potential impact of distraction on driving performance is well known and poses a safety concern – especially for individuals with cognitive impairments who may be clinically unfit to drive. The present study is the first to combine functional magnetic resonance imaging (fMRI) and eye-tracking during simulated driving with distraction, providing oculomotor metrics to enhance scientific understanding of the brain activity that supports driving performance. Materials and Methods: As initial work, twelve healthy young, right-handed participants performed turns ranging in complexity, including simple right and left turns without oncoming traffic, and left turns with oncoming traffic. Distraction was introduced as an auditory task during straight driving, and during left turns with oncoming traffic. Eye-tracking data were recorded during fMRI to characterize fixations, saccades, pupil diameter and blink rate. Results: Brain activation maps for right turns, left turns without oncoming traffic, left turns with oncoming traffic, and the distraction conditions were largely consistent with previous literature reporting the neural correlates of simulated driving. When the effects of distraction were evaluated for left turns with oncoming traffic, increased activation was observed in areas involved in executive function (e.g. middle and inferior frontal gyri) as well as decreased activation in the posterior brain (e.g. middle and superior occipital gyri). Whereas driving performance remained unchanged (e.g. turn speed, time to turn, collisions), the oculomotor measures showed that distraction resulted in more consistent gaze at oncoming traffic in a small area of the visual scene; less time spent gazing at off-road targets (e.g. speedometer, rear-view mirror); more time spent performing saccadic eye movements; and decreased blink rate. Conclusions: Oculomotor behaviour modulated with driving task complexity and distraction in a manner consistent with the brain activation features revealed by fMRI. The results suggest that eye-tracking technology should be included in future fMRI studies of simulated driving behaviour in targeted populations, such as the elderly and individuals with cognitive complaints – ultimately towards developing better technology to assess and enhance fitness to drive.